2009
DOI: 10.1128/cvi.00178-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the CervidTB STAT-PAK for the Detection of Mycobacterium bovis Infection in Wild Deer in Great Britain

Abstract: Deer are acknowledged as hosts of Mycobacterium bovis, the causative agent of bovine tuberculosis (bTB), and determining the prevalence of infection in deer species is one of the key steps in understanding the epidemiological role played by cervids in the transmission and maintenance of bTB in the United Kingdom. This study evaluated a rapid lateral-flow test for the detection of bTB in samples from wild deer species in the United Kingdom. Fallow deer (Dama dama), roe deer (Capreolus capreolus), and red deer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…In the absence of apparent confounding factors, the test specificities were higher than those in the current studies, ranging from 94.8 to 98.9% (3,9,14). There may be differences in sensitivity between species of deer due to different affinities of test reagents with antibodies from these deer, especially between Old World Cervus sp.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…In the absence of apparent confounding factors, the test specificities were higher than those in the current studies, ranging from 94.8 to 98.9% (3,9,14). There may be differences in sensitivity between species of deer due to different affinities of test reagents with antibodies from these deer, especially between Old World Cervus sp.…”
Section: Discussioncontrasting
confidence: 40%
“…The proportion of false positives is likely to increase with the decreasing prevalence of M. bovis-infected deer herds in various parts of the world, as improved strategies to control TB in these animals are implemented. Hence, the development of novel tests with enhanced specificity is imperative for more accurate detection of bovine TB in deer.The CervidTB STAT-PAK lateral-flow test (Chembio Diagnostic Systems, Inc., Medford, NY) has been evaluated using a number of different species of free-ranging wild deer (3,9,14). Although the test showed a high sensitivity for detecting M. bovis infection, it is not clear whether the test specificity is affected when testing sera from M. avium subsp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The new serological tests (RT and DPP) have also been evaluated in a number of studies with deer and found to perform well. The sensitivity and specificity of the RT for three common species of deer in the UK were 85.7% and 94.8%, respectively (Gowtage‐Sequeira et al., ), comparing well to an evaluation of the same test in fallow deer in Spain and the United States (Jaroso et al., ; Waters et al., ) and white‐tailed deer ( Odocoileus virginianus ) and elk in the United States (Lyashchenko et al., ; Waters et al., ). Similarly, the more recent DPP test gave a sensitivity of 79% and 91% in elk and fallow deer, respectively, at specificities approaching 100% (Waters et al., ).…”
Section: Serologymentioning
confidence: 82%
“…Mycobacterium bovis is also a well‐documented zoonotic agent, is highly virulent in both animals and humans and has a worldwide distribution. It principally affects the family Bovidae including buffaloes, bison, antelopes, goats and sheep but can also cause disease in other mammals such as pigs, horses, camels and wildlife as well as pet animals like dogs and cats (Thoen et al., ; Melinda et al., ; Rodwell et al., ; Drewe et al., ; Gowtage‐Sequeira et al., ; Shrikrishna et al., ; Chambers et al., ; Park et al., ; Lyashchenko et al., ; Greene, ; Olivier et al., ). In the United Kingdom, M. bovis is endemic in the wild badger population with spillover into farm animals, especially cow herds.…”
Section: Mycobacterial Disease and Zoonotic Disease Potentialmentioning
confidence: 99%